Online Learning Modalities in Dental Education during COVID-19 Pandemic - Pokhrel, Sadikchya (Journal of Nepalese Association of Pediatric Dentistry, 2021)
Remote learning on digital platforms has replaced conventional learning to alleviate the effects caused by the pandemic. Dental educational institutions had opted for alternative methods to continue with the academics to allow students to pursue their education even with the physical shutdown of schools worldwide. Embracing various challenges, remote learning has been implemented since over a year in many dental schools in Nepal. Although still practiced in many educational institutes, the efficacy of these new modalities, however, remains in doubt, especially in medical/ dental field, where practical and clinical practice is concerned.